Two new species of Xanthophius Motschulsky (Coleoptera: Staphylinidae, Staphylininae, Xantholinini) from China with notes on X. filum (Kraatz) - Zhou, Yu-Lingzi; Zhou, Hong-Zhang (Zootaxa, 2013)
This paper studies the taxonomy of the genus Xanthophius Motschulsky, 1860 (Coleoptera: Staphylinidae, Staphylininae, Xantholinini). Two new species are described from China: Xanthophius unicidentatus sp. n. from Yunnan, Zhejiang, Guangxi and Hainan, and X. gutianshanensis sp. n. from Zhejiang. The number of species of Xanthophius therefore increased to eight. The elaborate structures of the everted endophallus of X. filum (Kraatz, 1859) is described for the first time and illustrated with a color plate. A key to eight species and their geographical distribution map are provided. The type specimens of the new species are deposited in the Institute of Zoology, Chinese Academy of Sciences (IZ-CAS).